2001
DOI: 10.1111/j.1469-7793.2001.0771e.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustained stimulation of exocytosis triggers continuous membrane retrieval in rat pituitary somatotrophs

Abstract: 1. We studied the relationship between exocytosis and endocytosis in rat pituitary somatotrophs using patch-clamp capacitance, FM1-43 fluorescence imaging and amperometry.2. Stimulation of exocytosis through voltage-dependent Ca 2+ channels by depolarizations (1-5 s) increased the capacitance by 4.3 ± 0.9 % and the fluorescence by 6.6 ± 1.1 % (10 cells). The correlation between the capacitance and fluorescence changes indicated that the cell membrane and granule membrane added via exocytosis were stained with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 70 publications
(101 reference statements)
2
29
0
Order By: Relevance
“…To test this hypothesis further, we monitored cumulative exocytosis by using the FM 4-64 styryl fluorescent probe, which stains membranes (Betz et al, 1992;Smith and Betz, 1996;Kilic et al, 2001). If the ionomycin-induced decline in green fluorescence intensity is attributable to regulated exocytosis, this should be associated with the incorporation of the new vesicle membrane into the plasma membrane (Smith and Betz, 1996); therefore, the intensity of FM 4-64 fluorescence should increase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To test this hypothesis further, we monitored cumulative exocytosis by using the FM 4-64 styryl fluorescent probe, which stains membranes (Betz et al, 1992;Smith and Betz, 1996;Kilic et al, 2001). If the ionomycin-induced decline in green fluorescence intensity is attributable to regulated exocytosis, this should be associated with the incorporation of the new vesicle membrane into the plasma membrane (Smith and Betz, 1996); therefore, the intensity of FM 4-64 fluorescence should increase.…”
Section: Resultsmentioning
confidence: 99%
“…Using FM 4-64 to monitor cumulative exocytosis (Betz et al, 1992;Smith and Betz, 1996;Kilic et al, 2001), we found a Ca 2ϩ -dependent increase in total FM 4-64 fluorescence intensity.…”
Section: Calcium-dependent Exocytosismentioning
confidence: 94%
See 1 more Smart Citation
“…Smith and Neher, 1997), pancreatic β-cells (Eliasson et. al., 1996), melanotrophs (Thomas et al, 1994), corticotrophs (Lee and Tse, 2001) and somatotrophs (Kilic et. al., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To stimulate heterotrimeric G-proteins more specifically, cells were dialyzed with an aluminum fluoride solution that contained 120 mM KCl, 10 mM NaCl, 10 mM NaF, 0.03 mM AlCl 3 , 1 mM EGTA, 0.5 mM CaCl 2 , 2 mM MgCl 2 , and 10 mM HEPES/NaOH. Under these conditions, the concentration of AlF 4 Ϫ was 30 M (20 ] i was determined as described previously (21). The pH of all solutions was 7.25.…”
Section: Methodsmentioning
confidence: 99%